A Study on Durability of a Fragrance Finishing on Jute Fabric. Issue 11 (1st November 2020) - Ammayappan, Lakshmanan; Pan, Nimai Chandra; Chakraborty, Sujay; Khan, Amlesh
ABSTRACT: Literature information on development of jute-based home textiles with an esthetic appeal and sustainable fragrance still lacks. A fragrance finish has been applied on a bleached jute fabric and the durability of the fragrance against home laundering was assessed by subjective assessment, scanning electron microscopic (SEM), moisture regain (%), Fourier transform infrared spectroscopy (FTIR), and handle property. Results inferred that microencapsulated fragrance sustains on the jute fabric up to 10 washing cycles.